Nitrous Oxide and Serious Long-term Morbidity and Mortality in the Evaluation of Nitrous Oxide in the Gas Mixture for Anaesthesia (ENIGMA)-II Trial. (December 2015) - Leslie, Kate; Myles, Paul S.; Kasza, Jessica; Forbes, Andrew; Peyton, Philip J.; Chan, Matthew T. V.; Paech, Michael J.; Sessler, Daniel I.; Beattie, W. Scott; Devereaux, P. J.; Wallace, Sophie
Abstract : Background: The Evaluation of Nitrous Oxide in the Gas Mixture for Anaesthesia (ENIGMA)-II trial randomly assigned 7, 112 noncardiac surgery patients at risk of perioperative cardiovascular events to 70% N2 O or 70% N2 groups. The aim of this follow-up study was to determine the effect of nitrous oxide on a composite primary outcome of death and major cardiovascular events at 1 yr after surgery. Methods: One-year follow-up was conducted via a medical record review and telephone interview. Disability was defined as a Katz index of independence in activities of daily living score less than 8. Adjusted odds ratios and hazard ratios were calculated as appropriate for primary and secondary outcomes. Results: Among 5, 844 patients evaluated at 1 yr, 435 (7.4%) had died, 206 (3.5%) had disability, 514 (8.8%) had a fatal or nonfatal myocardial infarction, and 111 (1.9%) had a fatal or nonfatal stroke during the 1-yr follow-up period. Exposure to nitrous oxide did not increase the risk of the primary outcome (odds ratio, 1.08; 95% CI, 0.94 to 1.25; P = 0.27), disability or death (odds ratio, 1.07; 95% CI, 0.90 to 1.27; P = 0.44), death (hazard ratio, 1.17; 95% CI, 0.97 to 1.43; P = 0.10), myocardial infarction (odds ratio, 0.97; 95% CI, 0.81 to 1.17; P = 0.78), or stroke (odds ratio, 1.08; 95% CI, 0.74 to 1.58; P = 0.70). Conclusion: These results support the long-term safety of nitrous oxide administration in noncardiac surgical patients with known or suspected cardiovascular disease. Abstract : Nitrous oxide did not increase the risk of a composite primary outcome of death and major cardiovascular events at 1 yr in 5, 844 patients with cardiovascular disease recruited to the Evaluation of Nitrous Oxide in the Gas Mixture for Anaesthesia (ENIGMA)-II trial. These results support the long-term safety of nitrous oxide administration in noncardiac surgical patients with known or suspected cardiovascular disease.Supplemental Digital Content is available in the text.